Religion and Politics - John B Chethimattam (Journal of Dharma, 1982)
Today political institutions are facing a crisis, and religion which was the mainstay and guarantor of political authority in the past is not helping very much in facing the situation. While political authority is fast losing its credibility, religious fundamentalism is trying to usurp political power. What is the right relationship between religion and politics? In this issue of Dharma we wish to focus attention on this problem.